Proposed Business Strategy for Financial Services Industry Division in Markplus Institute to Increase Competitiveness in the Market - Devi, Tandya Vera; Dalimunthe, Gallang Perdhana (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The growing competitiveness in the market of professional training industry, particularly within the Financial Services Industry (FSI) Division of MarkPlus Institute, has prompted a strategic reassessment. This research aims to identify competitive advantages and propose a business strategy to enhance FSI’s market position. A qualitative approach was used to analyze internal and external factors. The tools like VRIO and Porter’s Generic Strategies supported the analysis. The findings highlight that political factors and industry rivalry are key external influences. Internally, FSI’s competitive edge include strong brand equity, a vibrant event and community ecosystem, and proprietary books and frameworks. The study concludes that MarkPlus Institute should offer a signature program aligned with regulatory needs, competitively priced, trend-relevant, and backed by brand trust, exclusive materials, high-quality facilitators and analysts to sustain competitive advantage.